Review of the state-of-the-art of exhaust particulate filter technology in internal combustion engines. (1st May 2015) - Guan, Bin; Zhan, Reggie; Lin, He; Huang, Zhen
Abstract: The increasingly stringent emission regulations, such as US 2010, Tier 2 Bin 5 and beyond, off-road Tier 4 final, and Euro V/5 for particulate matter (PM) reduction applications, will mandate the use of the diesel particulate filters (DPFs) technology, which is proven to be the only way that can effectively control the particulate emissions. This paper covers a comprehensive overview of the state-of-the-art DPF technologies, including the advanced filter substrate materials, the novel catalyst formulations, the highly sophisticated regeneration control strategies, the DPF uncontrolled regenerations and their control methodologies, the DPF soot loading prediction, and the soot sensor for the PM on-board diagnostics (OBD) legislations. Furthermore, the progress of the highly optimized hybrid approaches, which involves the integration of diesel oxidation catalyst (DOC) + (DPF, NO x reduction catalyst), the selective catalytic reduction (SCR) catalyst coated on DPF, as well as DPF in the high-pressure exhaust gas recirculation (EGR) loop systems, is well discussed. Besides, the impacts of the quality of fuel and lubricant on the DPF performance and the maintenance and retrofit of DPF are fully elaborated. Meanwhile, the high efficiency gasoline particulate filter (GPF) technology is being required to effectively reduce the PM and particulate number (PN) emissions from the gasoline direct injection (GDI) engines to comply with the future increasingly stricter emissions regulations. Graphical abstract: Highlights: Increasing stringent emission regulations mandate the use of particulate filters. Progress of DPF substrate, regenerations, and integrated systems are discussed. Impacts of the quality of fuel and lubricant on DPF performance are elaborated. High efficiency gasoline particulate filters reducing PM and PN are illustrated. Future perspectives of the advanced particulate filter technologies are described.